Unveiling Intersemiotic Relationships in Pakistani Children’s English Language Textbooks through Barthes’s Notion of Intertextuality - Kisaa Zahra; Hijab Zahra; Babar Khan; Sidra Lateef Shah; Sameen Aqeel (Social Science Review Archives, 2025)
This study looks at the intersemiotic relationships in Pakistani children’s English language textbooks through Barthes’s notion of intertextuality, recognizing that incorporating Barthes’s intertextuality in ESL young learners’ textbooks is a better way to learn and comprehend the English language. While there are many methods for teaching English language to ESL learners, however, there is a need to understand how intersemiotic relationships in children’s English books enhance their language learning. Therefore, this research aims to provide a comprehensive analysis of the intersemiotic relationships in Pakistani children’s English language textbooks through Barthes’s notion of intertextuality. In addition to answering the question: ‘How do semiotic elements (illustrations and visual aids) interact with the text to convey meaning through Barthes’ notion of intertextuality 1967 in the Cambridge Reading Adventures textbooks used by young ESL learners in Pakistan?’ this study also wields qualitative method to focus on the thematic analysis of the inter-semiotic and textual elements. Moreover, the study utilizes five of the Cambridge Reading Adventures textbooks used by young ESL learners in Pakistan for analysis. The findings of this study contribute to a deeper understanding of which language teaching method should be integrated for developing the competence of ESL learners. All in all, this research sheds light on the evolving nature of language pedagogy shift and intersemiotics. To conclude, the study's findings have implications for scholars of language pedagogy, teachers, and social sciences department.